Ritual and Sacred Space: The Role of Ritual in Shaping the El Shaddai Community - Makiling, Joven (Social Sciences and Development Review, 2025)
This study aims to examine the role of ritual in shaping sacred space and community within the El Shaddai fellowship. Using an ethnographic approach, observations were conducted over five consecutive Saturdays at Amvel City, Parañaque City, to identify and describe the rituals performed during the group’s weekly gatherings. The research found seven primary rituals, referred to as “spiritual activities,” which serve as essential components of the members’ spiritual lives. Additionally, the study highlights the role of the stage as a “sacred space” that functions as the focal point of ritual performance. The analysis reveals that ritual is not only a spiritual practice but also a form of communication that strengthens collective identity and unity within the community. This perspective aligns with James Carey’s Ritual Communication Theory, which posits that communication is a means of meaning-making and fostering participation in a faith-based community. Overall, the research demonstrates that both the performance of rituals and the presence of sacred space contribute to the spiritual development and social connection of El Shaddai members. This study may serve as a foundation for deeper analysis of the role of ritual in various religious communities in the Philippines.